Aortic Valve and Thoracic Aortic Calcification Measurements: How Low Can We Go in Radiation Dose?. Issue 1 (January 2017) - van Hamersvelt, Robbert Willem; den Harder, Annemarie M.; Willemink, Martin J.; Schilham, Arnold M.R.; Lammers, Jan-Willem J.; Nathoe, Hendrik M.; Budde, Ricardo P.J.; Leiner, Tim; de Jong, Pim A.
Abstract : Objective: This study aimed to determine the lowest radiation dose and iterative reconstruction level(s) at which computed tomography (CT)–based quantification of aortic valve calcification (AVC) and thoracic aortic calcification (TAC) is still feasible. Methods: Twenty-eight patients underwent a cardiac CT and 20 patients a chest CT at 4 different dose levels (routine dose and approximately 40%, 60%, and 80% reduced dose). Data were reconstructed with filtered back projection, 3 iDose 4 levels, and 3 iterative model-based reconstruction levels. Two observers scored subjective image quality. The AVC and TAC were quantified using mass and compared to the reference scan (routine dose reconstructed with filtered back projection). Results: In cardiac CT at 0.35 mSv (60% reduced), all scans reconstructed with iDose 4 (all levels) were diagnostic, calcification detection errors occurred in only 1 patient, and there were no significant differences in mass scores compared to the reference scan. Similar results were found for chest CT at 0.48 mSv (75% reduced) with iDose 4 levels 4 and 6 and iterative model reconstruction levels 1 and 2. Conclusions: Iterative reconstruction enables AVC and TAC quantification on CT at submillisievert dose.